The impact of retail investor attention on the returns, trading volume and volatility of non-fungible tokens - Aboobaker, Mishal (Department of Finance and Tax, 2024)
Non-fungible tokens (NFTs) increased in popularity dramatically in 2021 and the early parts of 2022. Individuals who trade NFTs are typically retail investors who obtain their information from public resources. Literature such as Kristoufek (2013), Nasir et al. (2019) and Li et al. (2021) shows that investor attention, especially retail investor attention, impacts the returns, volatility and trading volume of stocks and cryptocurrencies, although there is mixed evidence as to whether the impact on returns is negative or positive. This study evaluates whether retail investor attention impacts the returns, trading volume and volatility of NFTs. Drawing from studies including Da et al. (2011) and Kristoufek (2013) that suggest increased internet searches reflect heightened investor attention, a Google Search Volume index comprising 13 popular search terms related to NFTs is created to quantify investor attention on this asset class. The returns, trading volume and volatility of six NFT collections are examined. Using ordinary least squares, regression results show that contemporaneous and lagged investor attention has only a minor impact on NFT returns, volatility and trading volume. Wavelet analysis confirms that the association between investor attention and returns, volatility and trading volume is small for the six NFT collections but, where there is an association, it is predominantly over medium- and long-term horizons (whereby 33 to 128 days are defined as the medium run and values greater than 129 days are considered to represent the long run). Furthermore, it revealed some evidence of a relationship in the opposite direction (i.e. investor attention may respond to market movements). Overall, these results suggest that attention on this new asset class has little impact on the trading, pricing or volatility of NFTs.